Sikap Guru Terhadap Perubahan Kurikulum KTSP 2006 Ke Kurikulum 2013: Indonesia - Sulaiman; Elsunarti; Firdaus; Juni Kardi (Sekolah Tinggi Ilmu Tarbiyah Al- Kifayah Riau, 2019)
The phenomenon of teacher anxiety about the change in the curriculum from KTSP to 2013 curriculum is almost everywhere, including teachers in public elementary schools in Sail District, Pekanbaru City. On average the teachers lack positive attitudes, in other words, tend to have a negative view of the curriculum change from KTSP 2006 to the 2013 curriculum. Some teachers think that every time the government changes, the curriculum changes too. Some teachers are worried about issues that are developing about the 2013 Curriculum, such as a reduction in subject teachers. This research is descriptive with a total population of 122 teachers from 8 SDN Se District Sail. The sample was taken as much as 15% of the population, namely 17 teachers randomly (random). To collect data, a questionnaire with a Likers scale was used. Then the data is processed and analyzed with the percentage descriptive qualitative data analysis technique. Based on the results of the analysis carried out, this study can conclude as follows: (1) The attitude of the teacher towards the change in the curriculum from KTSP 2006 to the 2013 Curriculum in SDN Se-Subdistrict Sail Pekanbaru City by 68.5% so that it is categorized as Bad; (2) The factors that influence teachers' attitudes towards curriculum changes from KTSP 2006 to 2013 Curriculum in SDN Se-Subdistrict, Pekanbaru City, namely: a) internal factors (from within) teachers, including 1) Teacher teaching experience; Work motivation; and educational background; b) External factors (from outside) the teacher, including The leadership of the principal; Teacher welfare; Work environment climate